Intersectionality Under Debate in a Globalized World: A Critical Review of the Construction of Democratic Societies Through the Interrelation of Gender, Race, and Cultural Diversities - Elena Montejo-Palacios; María del Consuelo Díez-Bedmar; Pablo Cantero-Castelló (Social Sciences)
Teacher education is paramount for nurturing democratic, critical, and participative citizenship. Educators should approach identity formation from an intersectional perspective, encompassing sex–gender, racial, and cultural diversities. This perspective highlights social inequalities and challenges the power structures that sustain them. Teachers play a crucial role in shaping and reflecting on these identities since their responsibilities extend beyond knowledge transmission. Their ability to incorporate intersectional perspectives into teaching influences students’ understanding of intersectionality, thereby supporting the development of inclusive identities and promoting democratic citizenship. This article opens with the results of research on how trainee teachers acquire competencies in feminist critical visual literacy. Following this review, we analyzed educational materials to examine stereotypes, racism, and the invisibility of racialized and cultural minority communities. We also addressed the identification and counteraction of hate speech targeting the LGTBIQ+ community as well as different gender-based violence. Comparative data from participating universities provide insights into the critical skills of pre-service teachers across international contexts. This study highlights an urgent need for further research into integrating intersectionality in teacher training, supported by educational policies that strengthen critical competencies through a holistic, gender- and race-sensitive approach aimed at social justice. These initiatives would promote an education system responsive to multifaceted diversities.